Analisis Penentuan Sektor Unggulan Perekonomian Wilayah Kabupaten Asahan - M. Dzaki Wiranda (Economie: Jurnal Ilmu Ekonomi, 2023)
Regional development planning in the regional economy is a regional development policy with limited resources. As a result, it must concentrate on the growth of sectors that have a significant multiplier effect on other sectors or the sector as a whole. The GRDP of the Asahan Regency economy will increase between 2017 and 2021 (except in 2020 which will decrease due to the co-19 pandemic). The purpose of this research is to identify the most successful sectors in Kabupaten Asahan and ways to improve and develop these sectors to make them even more successful. Klassen Typology Analysis, Location Quotient (LQ), and Shift Share are the analytical tools used. The results show that the agriculture, forestry and fishery sectors, the manufacturing sector, and the wholesale and retail trade sector are three leading sector analysis tools that have the potential to be developed based on the results of this analysis; the car and motorcycle maintenance industry as well as other services The remaining four industries are industries that have the potential to be developed further in an effort to boost the economy of Asahan Regency.